Avaliação do desempenho dos centros de especialidades odontológicas regionais do Ceará - Mendes, Gemakson Mikael (2024)
Specialized care in the state of Ceará is regionalized through public consortia agreed between municipalities in the same region and the state. Each consortium is governed by program contracts that help monitor health services in its region. The present study aimed to carry out a performance assessment of Regional CEOs in the state of Ceará. A descriptive, observational and quantitative study was carried out based on trends in the “ICGM” index for the specialties of endodontics, surgery, periodontics and prosthesis in the 22 Regional CEOs of Ceará through a historical series between 2014 and 2023. The services were also evaluated in the years 2019 (pre-pandemic) and 2023 (post-pandemic), by classifying their performance and patient absence rates. Secondary data relating to production were collected from the Ambulatory Information System (SIA/SUS) through the IntegraSUS website, while data relating to absent patients were collected from the Integrated Health Management System (SIGES), in the state of Ceará. A stationary ICGM trend was identified over a 10-year period for almost all specialties, with the exception of periodontics, which showed a decreasing trend from 2019-2021, followed by an increasing trend in 2022-2023. Endodontics and surgery specialties showed lower rates of achieving goals, while periodontics procedures emerged with values above the average. The number of prostheses installed will be close to the number of prostheses manufactured. Furthermore, the state average performance in all specialties fell in 2023 when compared to 2019, revealing that services have not returned to their pre-pandemic performance. This behavior cannot be explained by the lack of patients attending appointments, as the absentee rate remained similar in both years. Periodontics and prosthesis targets are at odds with production capacity as they exceeded the minimum targets set by the Ministry of Health. The inferior performance of endodontics and surgery highlights the need for strategies to improve these services, from the quality of management of work processes and the reduced dental clinic to the population's access barriers to care.